Prática docente e justiça: educação em valores morais no ensino fundamental - Couto, Leandra Lúcia Moraes (2013)
In this study, we dedicate ourselves to investigate the judgments of teachers on the teaching of the moral value of justice in their pedagogical practices. Furthermore, we propose to check whether such practices are modified due to the school year for which the participant teaches. To do so, we interviewed 23 elementary school teachers, 11 teachers of 1st year and 12 of the 5th year, from public schools located in lower-class neighborhoods in the city of Vitória, Espírito Santo. We conducted individual interviews, according to the Piagetian clinical method. Data analysis was performed based on the theory of Piaget and the systematization proposed by Delval. We analyze the conceptions of justice of the teachers, the motivations for teaching justice and the procedures that the respondents consider they use to teach this moral value. The results support the view that the conception of justice of the teachers is mainly related to the issue of individual s rights. Regarding justice, all the professionals believe they teach this moral value in their pedagogical practices. Regarding the motivations for this practice, we noticed that the teachers teach justice mainly because this is a responsibility of the school. Meanwhile, about the procedures for teaching justice, we noticed that most of them are means considered as authoritative, verbally and in action, i.e., are grounded in imposing practices. Moreover, most of the procedures are based solely on the oral language of the teachers. Most participants justify the procedures adopted in the teaching of justice as focusing the student, i.e., dealing with practices that have as their basis the students. However, when we analyzed the methods used by the interviewees, we found that most of them concerns methods with the use of imposition, which may not favor the said active procedures and, probably the moral development of students. Regarding the data found on the school years studied, we emphasize that the teachers who teach the 5th grade mention more procedures based on imposing practices. Finally, it is worth saying that the participants of the 1st year are the ones who justified the most procedures with a focus on the student. In general, the data from our research show that although the conceptions of justice of the participants have predominant characteristics of autonomous morality, most of the procedures used by them in teaching the alluded value can not foster the development of autonomy in students, as they are grounded in imposing practices. With this study, we hope to contribute so that public policies are implemented in order to improve the quality of education in moral values in schools, especially regarding the teaching about justice. Thus, we emphasize the need for continuous education on the teaching of justice, designed and programmed to develop autonomous individuals